SHM_120458_HST_3D Vendel XIV Helmet - Lernestål, Erik; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of the Vendel XIV helmet, an iron helmet with bronze fittings and gilding. The helmet was excavated from an Iron Age boat grave (Vendel XIV) in Vendel Parish, Uppsala County and is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=848

Link to Sök I Samlingarna

https://samlingar.shm.se/object/A20FACD7-D39E-4EE5-9B72-16601649C9A3
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; 3D Model; Museum Object; Dynamic Collections; Vendel; Swedish Iron Age; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi